OPTIMIZING CORN HARVEST WASTE AS A COMMUNITY ECONOMIC, IMPROVEMENT IN TAWANGREJO VILLAGE, GEMARANG, DISTRICT, MADIUN REGENCY - Soemarsono, Prinintha Nanda; Nabila, Lady Savita; Syafi'ah, Kamilatus; Pratama, Rehan Meihendra; Pramesti, Mutiara Putri; Kusuma, Juan; Prananda, Ariel Syalia; Cahyani, Larasati Puji; Hapsari, Aulia Arum; Maulana, Isya' Putra (Universitas Airlangga, 2024)
Corn is the second largest commodity in Tawangrejo Village, Gemarang District, Madiun Regency with a harvest reaching 3 tonnes in 2023. The large corn harvest is in line with the corn waste produced at the end of each harvest period. Until now, corn waste is still used as animal feed in small quantities and the rest is burned, resulting in air pollution around Tawangrejo Village. The work program of